Utilization of Digital Marketing for MSME Players as Value Creation for Customers during the COVID-19 Pandemic - Finny Redjeki; Azhar Affandi (International Journal of Science and Society, 2021)
The Covid-19 pandemic since the beginning of 2020 has changed all aspects of people's lives. The community must start a new life adaptation where the implementation of health protocols is not only mandatory but also a lifestyle trend. One of the new habits that many people are starting to implement is online shopping. This is an opportunity for MSMEs in Indonesia to be able to take this opportunity so that they can develop and sustain their business in the midst of the COVID-19 pandemic. Therefore, it is necessary for MSME players to be introduced to Digital Marketing. The goal of this study is to introduce the deployment of small and medium-sized enterprises in the MSME sector during the COVID-19 pandemic. This review takes a qualitative approach, using a literature review, to examine and solve research content issues. The results of the research show that digital marketing is very helpful for MSME players in Indonesia because with the various benefits that digital marketing has, it can increase the sales turnover of MSME players. However, digital marketing has not been widely applied to the MSME sector in Indonesia due to several factors, including not yet technological literacy, inadequate supporting facilities to Indonesia's geographic conditions which become obstacles. Therefore, researchers recommend a few simple things how to start a business with digital marketing, such as starting to determine marketing goals, marketing targets, determining the digital platform to use; determine the budget, and create content that can attract consumer attention. In this study, the authors also describe the added value obtained by customers who use digital marketing.